2014
DOI: 10.1016/j.crohns.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Delving into disability in Crohn's disease: Dysregulation of molecular pathways may explain skeletal muscle loss in Crohn's disease

Abstract: The reduced muscle mass in CD may be explained, in part, by impaired activation of muscle protein synthesis pathways, notably the IGF1-Akt pathway. Normal vitamin D levels and regular exercise may be protective in CD against this trend, though confirmatory longitudinal studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…29 A condition characterized by systemic inflammation and malabsorption is likely to be associated with macronutrient malnutrition particularly with reduced muscle mass as demonstrated for instance in Crohn's disease. 30,31 Few in this cohort were protein or energy malnourished comparing with healthy population norms, and more were overweight or obese. This might reflect the availability of food in the community, and the eating habits and food choices made by the individuals, whereby malabsorption and increased consumption of energy might be easily offset by excessive consumption.…”
Section: Discussionmentioning
confidence: 94%
“…29 A condition characterized by systemic inflammation and malabsorption is likely to be associated with macronutrient malnutrition particularly with reduced muscle mass as demonstrated for instance in Crohn's disease. 30,31 Few in this cohort were protein or energy malnourished comparing with healthy population norms, and more were overweight or obese. This might reflect the availability of food in the community, and the eating habits and food choices made by the individuals, whereby malabsorption and increased consumption of energy might be easily offset by excessive consumption.…”
Section: Discussionmentioning
confidence: 94%
“…Although vitamin D supplementation increases muscle strength and balance in some populations for example in the elderly (104) data in Crohn's disease are not as widely available. In a cross-sectional study, van Landenberg et al (105) reported that high 25(OH)D and physical activity may protect against reduced muscle mass (90) . Conversely Salacinski et al (106) were unable to show a relationship between 25(OH)D levels and muscle strength in Crohn's disease.…”
Section: Clinical Studies; Association Between 25-hyroxyvitamin D Levmentioning
confidence: 99%
“…32 A decrease in the concentration of IGF -1, hormone responsible for normal growth of bones and muscles, as well as a decrease in the level of IGFBP -3 are among the factors contributing to muscle weakness and osteoporosis in patients with IBD. 28,31,33,34 These abnormalities intensify with prolonged disease duration. Van Langenberg et al 33 found that a decrease in the IGF -1 level was associated with muscle weakening in patients with CD; however, disease duration was not considered and the analysis did not include patients with UC.…”
Section: Patientsmentioning
confidence: 99%
“…28,31,33,34 These abnormalities intensify with prolonged disease duration. Van Langenberg et al 33 found that a decrease in the IGF -1 level was associated with muscle weakening in patients with CD; however, disease duration was not considered and the analysis did not include patients with UC. Among the studies of osteoporosis in patients with IBD, only Koutroubakis et al 34 analyzed correlations between the IGF -1 and IGFBP -3 levels and the intensification of osteoporosis in patients with IBD.…”
Section: Patientsmentioning
confidence: 99%